INFORMATION RATES OF INFORMATION LEAKAGE FROM MONITOR SCREENS ON RARE CRYSTAL STRUCTURES - Yevgrafov , Dmutro; Yaremchuk, Yurii (Ukrainian Scientific Journal of Information Security, 2022)
The spectral representation of information leakage signals from monitor screens, on which one of the letters of the Ukrainian alphabet is displayed, is considered. It is shown that even for a small resolution of the spectral representation of letters, they differ for two similar-looking letters. The scheme of studies of spurious electromagnetic radiation and interference is substantiated, which makes it possible to distinguish letters on the monitor screen depending on the power of the spectral components of the leakage signals. A program for processing images of signal spectra is considered, which makes it possible to compare the spectral components of leakage signals for different letters. The calculated and real spectra of leakage signals are compared and a conclusion is made about the correctness of using the models of information leakage signals, depending on its content. The calculation of the most informative frequencies of information leakage signals for various letters of the Ukrainian alphabet, depending on the standard sizes of fonts and operating modes of the monitor on rare-crystal structures, has been substantiated. Recommendations are given on the simplest ways to counter information leakage from monitor screens associated with a change in the frame rate according to a pseudo-random law.